Mental health and early adolescent: a prevalence study - Zahari, Solehudden Shaatibi; Aziz, Nur Wal Affa; Hamdan, Fatin Sahira; Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida (2018)
Prevalence of mental health problems among children and adolescent is increasing in trend as reported in National Health Morbility Survey (NHMS)